The development of livelihoods and career promotion for the quality of life of the elderly in new normal era in Roi Et, Khon Kaen, Maha Sarakham, and Kalasin provinces - Dechanubeksa, Natapasa; Arsasri, Kunteera; Srisawangwong, Papapit; Thongkam, Parinya (Journal for Developing the Social and Community, 2025)
Background and Aims: Given Thailand’s inevitable transition into a fully aged society, it is crucial to holistically enhance quality of life among older adults to support sustainable national development. This study aims to: (1) examine the factors related to the development of livelihoods, career promotion, and the quality of life in the new normal era among older adults in Roi Et, Khon Kaen, Maha Sarakham, and Kalasin provinces; (2) investigate the relationships between the factors of livelihoods development, career promotion, and the quality of life in the new normal era among older adults in the four provinces; (3) analyze the influence of livelihoods development and career promotion on quality of life in the new normal era among older adults in the four provinces; and (4) develop guidelines for improving quality of life in the new normal era. Methodology: This research was conducted using a mixed method. The quantitative approach was collected through questionnaires from 200 elderly participants (50 per province), selected through convenience sampling. Analysis included descriptive statistics, multiple correlation analysis, and multiple regression analysis. Subsequently, a life quality development activity was implemented, and additional data were collected both quantitatively by questionnaires and qualitatively by in-depth interviews on the satisfaction of activities from elderly participants, with five participants per province selected by purposive sampling. Results: Older adults in the four provinces perceived high levels of support in livelihoods development, career promotion, and quality of life. All studied factors were positively and significantly correlated with quality of life. The analysis of Living livelihoods development and career promotion found that living conditions, occupational knowledge, financial status, welfare, and digital media literacy significantly influenced the quality of life of the elderly at the 0.05 level. Based on these findings, two main development activities were designed: (1) the livelihoods development activity, focusing on living condition, financial literacy, welfare access, and media and technology awareness; and (2) the career promotion activity, focusing on enhancing occupational knowledge. Participant satisfaction with the quality-of-life development activities was rated very high, aligning with qualitative findings that highlighted the importance of all factors in enhancing quality of life in the new normal era. Conclusion: Guidelines for improving elderly quality of life in the new normal era include: (1) promoting knowledge and understanding of living condition development, covering safe and comfortable home and surrounding environment management; financial literacy in daily spending, lifelong financial planning, and income generation; basic awareness of welfare rights and related agencies; and digital literacy, including the use of basic technology and awareness of its benefits and risks; and (2) support career development by enhancing appropriate job-related knowledge. Additionally, support should be provided for fundamental aspects essential to elderly well-being, such as nutrition, healthcare, and physical exercise.